A COMPARISON OF THE ACADEMIC WORD LIST AND THE ACADEMIC VOCABULARY LIST: SHOULD THE AVL REPLACE THE AWL? - Gholaminejad, Razieh; Anani Sarab, Mohammad Reza (TEFLIN Journal, 2021)
In this commentary, we begin with the discussion on a brief history of academic wordlists. Adopting a comparative perspective, then, the merits and demerits of the Academic Word List (AWL) (Coxhead, 2000) and its competing counterpart the Academic Vocabulary List (AVL) (Gardner & Davies, 2014) are presented. We also explore whether the AWL can still be considered as "the best list” (Nation, 2001, p. 12) for improving academic words, or whether its counterpart is reasonably "the most current, accurate, and comprehensive list” (Gardner & Davies, 2014, p. 325). The comparison was made in terms of twelve aspects: corpus size, types of corpus texts, sources of corpus texts, text balance, disciplines included, counting unit, wordlist items, method for excluding highfrequency words, minimum frequency, method for excluding technical words, sequence of list items and lexical coverage. The comparison reveals that the AVL is far from complete and cannot replace the AWL. The results of the comparison can have implications for practitioners and course developers.